Дентальная объемная томография в решении некоторых задач стоматологии и челюстно- лицевой хирургии (Эндодонтия Today, 2020)
Dental computer tomography is a modern radiologic method that allows to obtain a comprehensive diagnosis of the state of dental and oral-facial system, which is important in all areas of dentistry and maxillofacial surgery. Due to the high image quality, features of the software, the method allows to diagnose various diseases and conditions of teeth and jaws, to plan treatment and evaluate the effectiveness of therapeutic measures.